Polyhydroxyalkanoates synthesis by halophiles and thermophiles: towards sustainable production of microbial bioplastics - Obruča, Stanislav; Dvořák, Pavel; Sedláček, Petr; Koller, Martin; Sedlář, Karel; Pernicová, Iva; Šafránek, David (Biotechnology advances, 2022)
Polyhydroxyalkanoates (PHA) are microbial polyesters produced by numerous prokaryotes. These materials are generally considered to be renewable and biodegradable alternatives to petrochemical polymers in numerous applications. PHA are accumulated by microbial cells in form of intracellular granules primarily as storage compounds; nevertheless, numerous recent reports also highlight the importance of PHA for the stress robustness of bacteria. Therefore, in this review, we focus on summarizing current knowledge on PHA accumulation in halophiles and thermophiles - prokaryotic microorganisms adapted to high salinity and high temperature, respectively. Utilization of extremophiles for PHA production brings numerous benefits stemming especially from the enhanced robustness of the process against contamination by common mesophilic microflora as a basement of the Next-Generation Industrial Biotechnology concept. Further, recent advances and future perspectives in metabolic engineering and synthetic biology of halophiles and thermophiles for PHA production improvement are also summarized and suggested. Facts and ideas gathered in this review hold a promise that biotechnological production of PHA by extremophiles can be sustainable and economically feasible enabling PHA to enter the market massively and compete with non-biodegradable petrochemical polymers in suitable applications.
Keywords: Metabolic engineering and synthetic biology; Metabolic Engineering; Biotechnological production of polyhydroxyalkanoates; Thermophiles; Biotechnology; biotechnologie; Bacteria; Archaea; metabolické inženýrství; Halophiles; Stress robustness; polyhydroxyalkanoáty; Adaptation; vysoká teplota; Hot Temperature; Polyhydroxyalkanoates